Toward a regional exchange rate regime in East Asia - Masahiro Kawai (Asian Development Bank Institute (ADBI), 2007)
Deepening market-driven economic integration in East Asia makes intraregional exchange rate stability across the region increasingly desirable and necessary. This paper suggests that East Asia's emerging economies begin with a currency basket system based on the G3 (US, Euro area and Japanese) or G3-plus (including emerging East Asian) currencies as a monetary policy anchor. This arrangement will enable all East Asian currencies to collectively appreciate vis-à-vis the US dollar, while maintaining intraregional rate stability, in the event of continuous surges of capital inflows to East Asia or a rapid unwinding of global payments imbalances. Such a system would contribute as an initial step to an East Asian monetary zone. After sufficient convergence and with stronger political commitment, East Asia may agree on more rigid intraregional exchange rate stabilization schemes through, for example, an Asian Snake or an Asian Exchange Rate Mechanism.
Keywords: F32; F33; F42; 330; Exchange rate arrangement in East Asia; yen and yuan; new Bretton Woods system; G-3 or G3-plus currency basket regime; Asian currency unit (ACU); Wechselkurssystem; Kapitalmobilität; Yen; Währung; Chinesisch; Internationale Währungspolitik; Ostasien